The structural shift of Singapore's external trade in the last decade. - Chong, Poh Lin. (2009)
This paper seeks to examine the structural shift in Singapore’s external trade, through a study on the changes in trade shares, for the period 1998 to 2007. It is divided into domestic exports and imports, concentrating on SITC one-digit and two-digit merchandise trade data. We identified Singapore’s major trade partners and top twenty trade commodities for both exports and imports. This research paper further focused on case studies for three commodities, which are SITC 54 (Medicinal and pharmaceutical products), SITC 75 (Offices and Data Machines) and SITC 77 (Electrical Machinery and Nes), as they showed the most significant changes in trade shares. International Competitive Coefficient (ICC) Index is used for each case study to analyse trade competitiveness and stages of development, whereas Shift-share analysis is used to examine the trend of Singapore’s export market growth.